The Use of Demonstration Methods in Improving Maharah Kalam at al Khalifah Sarolangun Islamic Junior High School - Zulfadli Zulfadli; Anwar Sanusi; Neldi Harianto; Salman Jufri; Mar'atun Sholiha (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
This study aims to identify the process and strategies of using thedemonstration method to improve mahārah al-kalām (Arabic speaking skills) and to determine the obstacles faced by students at SMP IT Al-Khalifah Sarolangun. This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The results indicate that the main factors affecting students’ Arabic speaking skills include limited vocabulary mastery, lack of repetition (murāja‘ah), low motivation, and insufficient time and facilities. The application of the demonstration method by teachers, such as performing objects or simple conversations, successfully increased student engagement in learning and improved vocabulary comprehension. However, the effectiveness of this method largely depends on students’ learning motivation as well as support from their families and school environment. This study is expected to serve as a reference for Arabic teachers to be more creative in applying teaching methods, particularly the demonstration method, to enhance students’ Arabic speaking skills.